Activation of Na+/H+ exchanger other than formation of transmembrane pore underlies the cytotoxicity of nematocyst venom from Chrysaora helvola Brandt jellyfish. (July 2017) - Fan, Lanlan; Luo, Jun; Li, Xiaoyong; Chen, Ming; Shu, Wei; Qu, Xiaosheng
Abstract: We previously reported unexpected apoptosis-like cell death induced by nematocyst venom (NV) from Chrysaora helvola Brandt ( C. helvola ) jellyfish. To assess whether the pore formation mechanism underlay the action of NV, the change in cell membrane permeability was studied in both chicken erythrocytes and human CNE-2 cells. Initially, paradoxical results were derived from osmoprotectant protection assays. Polyethylene glycol (PEG)2000, which completely inhibited the NV induced hemolysis, failed to protect CNE-2 cells. Detailed experiments showed that PEG protection from hemolysis is concentration dependent and indicated caution when estimating the pore size formed by NV with the osmotic protection method. NV-treated CNE-2 cells remained impermeable to dyes with various molecular weights (MWs) (622.6–40, 000 Da). Furthermore, membrane depolarization and selective permeability to Na + other than K + were induced in CNE-2 cells. No oxidative damage to the cell membrane was detected. Amiloride, an inhibitor of Na + /H + exchanger (NHE), substantially protected both CNE-2 cells and erythrocytes from NV. Combined with the previously reported increase in intracellular pH, we supposed that NV activated plasma membrane NHE without forming transmembrane pores. Interestingly, glutathione (GSH) showed significant protection to CNE-2 cells while potentiating the hemolytic power of NV. This finding may suggest a key role of reactive oxygen species (ROS) in the cytotoxicity of NV. To the best of our knowledge, this is the first report that a hemolytic jellyfish venom acts through NHE in a manner other than compromising membrane integrity. The current work provides new insight into the arsenal of toxic jellyfishes. Highlights: NV from C. helvola jellyfish induced selective permeability to Na + on CNE-2 cells. No oxidative damage to the cell membrane of CNE-2 was detected. The cytotoxicity and hemolytic activity of NV from C. helvola jellyfish can be prevent by amiloride. Glutathione can prevent the cytotoxicity of NV from C. helvola jellyfish but potentiate its hemolytic activity.